Distribution and excretion of cadmium and nickel after simultaneous exposure and the effect of N-benzyl-D-glucamine dithiocarbamate on their biliary and urinary excretion - Cikrt, M; Bláha, K; Nerudová, J; Bittnerová, D; Jehlicková, H; Jones, M M (Journal of toxicology and environmental health, 1992)
A rat model for combined exposure to cadmium and nickel is presented that involves the administration of drinking water containing these elements over a period of 90 d. Coadministration of these two ions in drinking water leads to brain levels of both elements that are significantly higher than results from the administration of equal doses of the metals individually. The enhanced biliary excretion of cadmium in rats given sodium N-benzyl-D-glucamine dithiocarbamate (BGDTC) is almost twice as great in those animals given cadmium and nickel as in those animals given cadmium only. The excretion of nickel is reduced by the administration of this chelating agent. Although equal amounts of nickel and cadmium were administered to these animals, liver and kidney cadmium levels were approximately 100 times greater than the corresponding nickel levels. The results suggest that combined exposure to these elements may lead to enhanced levels of nickel and cadmium in the brain and a level of nervous system damage not predictable from information obtained under conditions of exposure to only one of these elements.
Keywords: sorbitol; Thiocarbamates; injekce intraperitoneální; thiokarbamáty; Body Weight; Cadmium; aplikace orální; Drinking; Tissue Distribution; zvířata; chelátory; Injections, Intraperitoneal; nikl; Bile; Rats, Inbred Strains; Animals; inbrední kmeny potkanů; Chelating Agents; Administration, Oral; Liver; Female; Rats; tkáňová distribuce; ženské pohlaví; Sorbitol; Drug Interactions; Brain; ledviny; krysa rodu Rattus; žluč; pití; Nickel; kadmium; lékové interakce; játra; Kidney; tělesná hmotnost; mozek